PENGARUH KINERJA LINGKUNGAN, SIZE, PROFITABILITAS, UKURAN DEWAN KOMISARIS, PROFILE,LEVERAGE, dan KONSENTRASI KEPEMILIKAN PERUSAHAAN TERHADAP CSR DISCLOSURE DI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) tahun 2010-2012 - Khadifa, Ramanitya; Chariri, Anis (Diponegoro Journal of Accounting, 2014)
The aim of this research was to examine the effect of environmental performance, company size, profitability, profile, size of board commisioner, leverage, and concentration of corporate ownership toward corporate social responsibility (CSR) disclosure of manufacturing company. Dependent variable in this research was CSR disclosure.The population of this research is all of the manufacturing company listed in Indonesia Stock Exchange during 2010-2012. Total sample of this research was 104 companies. The collection of research data used purposive sampling method. the data analysis method used is analysis regression and descriptive statistics.The result showed that partially environmental performance and profile has significantly influence toward CSR disclosure. meanwhile partially company size, profitability,, board of commisioners, and leverage was not significantly influence toward CSR disclosure. and the last is concentration of corporate ownership has negative significant influence toward CSR disclosure.